Entre as várias vidas dos gatos e as muitas identidades dos camaleões: as comunidades tradicionais do Cerrado Mineiro: Among the various lives of cats and the many identities of chameleons: the traditional communities of the Cerrado - Minas Gerais State/Brazil (Élisée - Revista de Geografia da UEG, 2020)
Este texto apresenta elementos sobre a trajetória histórica de ocupação do Cerrado, refletindo sobre como esse processo contribuiu para a formação das comunidades tradicionais dos territórios que compõem esse bioma. Entendemos que o modo de vida dessas comunidades tem sido ameaçado por um conjunto de transformações ocorridas ao longo do século XX, sendo que tais ameaças impactam as comunidades também contribui para sua organização e para o desenvolvimento de alternativas coletivas de manutenção social e cultural.Abstract: This text presents elements on the historical trajectory of occupation of the Cerrado, reflecting on how this process has contributed to the formation of traditional communities in the territories that make up this biome. We understand that the way of life of these communities has been threatened by a series of transformations that have occurred throughout the 20th century, and these threats also impact the communities and contribute to their organization and to the development of collective alternatives for social and cultural resistance.Keywords: Traditional communities. Thick. Environmental History.Resumen: Este texto presenta elementos sobre la trayectoria histórica de la ocupación del Cerrado, reflexionando sobre cómo este proceso contribuyó a la formación de comunidades tradicionales en los territorios que conforman este bioma. Entendemos que el modo de vida de estas comunidades se ha visto amenazado por una serie de transformaciones que se han producido a lo largo del siglo XX, y estas amenazas también afectan a las comunidades y contribuyen a su organización y al desarrollo de alternativas colectivas para el mantenimiento social y cultural.Palabras clave: Comunidades tradicionales. Grueso. Historia ambiental.
Keywords: Comunidades tradicionales. Grueso. Historia ambiental.